Acute Hyperglycemia May Induce Renal Tubular Injury Through Mitophagy Inhibition - Wang, Jingyu; Yue, Xiaodan; Meng, Cheng; Wang, Ziyan; Jin, Xiaofang; Cui, Xiao; Yang, Juhong; Shan, Chunyan; Gao, Zhongai; Yang, Yanhui; Li, Jing; Chang, Bai; et al. (Frontiers in Endocrinology, 2020)
Aim: Acute hyperglycemia is closely related to kidney injury. Oxidative stress activation and notable mitochondria damages were found under acute hyperglycemia treatment in our previous work. In the present study, we explored the dose-effect relationship and the pivotal role of mitophagy in acute hyperglycemia induced tubular injuries. Methods: 40 non-diabetic SD rats were randomly divided and treated with different concentrations of hyperglycemia respectively during the 6h-clamp experiment. Renal morphological and functional alterations were detected. Rat renal tubular epithelial cells were treated with different concentrations of glucose for 6 hours. Markers and the regulation pathway of mitophagy were analyzed. Results: Significant tubular injuries but not glomeruli were observed under both light and electron microscope after acute hyperglycemia treatment, which manifested as enlargement of tubular epithelial cells, disarrangement of epithelial cell labyrinths and swelling of mitochondria. Urinary microalbumin, β2-MG, CysC, NAG, GAL and NGAL were increased significantly with the increase of blood glucose (P < 0.05). ROS was activated, mitochondrial membrane potential and LC3-II/LC3-I ratio were decreased but P62 and BNIP3L/Nix were increased in hyperglycemia groups (P < 0.05), which were reversed by AMPK activation or mTOR inhibition. Conclusion: Acute hyperglycemia causes obvious tubular morphological and functional injuries in a dose-dependent manner. Acute hyperglycemia could inhibit mitophagy through AMPK/mTOR pathway, which would aggravate mitochondria damage and renal tubular impairment.